Spiral to disaster - Nettles, John; Higgins, Bryn (Disaster (Television program), 2006)
Re-enactment of the destruction of the Piper Alpha oil rig in an explosion on July 6, 1988. The design of the platform is examined, together with the sequence of events that magnified the disaster.